Comparative study of CURB-65 and expanded CURB-65 score in community acquired pneumonia in a tertiary care hospital of Assam - Das, Parag Kumar; Phukan, Jayanta Dhekial; Sharma, Suresh; Goswami, Debasish; Yepthomi, Atovili K. (International Journal of Advances in Medicine, 2022)
Background: Community acquired pneumonia is one of the leading causes of morbidity and mortality in developing countries like India. The presentation of CAP may range from mild pneumonia characterized only by fever and productive cough to severe pneumonia leading to respiratory distress and sepsis syndrome requiring management in ICU. Any delay in ICU admission has been shown to be associated with increased mortality. This study was conducted to compare Expanded CURB-65 with CURB-65 scoring system in a tertiary care centre in Assam for early stratification of patients with CAP based of severity and expected prognosis. Methods: This hospital based prospective study was conducted between September 2020 to August 2021, and a total of 100 patients were taken and followed up form admission to up to 30 days. CURB65 and expanded CURB 65 score was calculated for each patient and the accuracy of each score was statistically compared. Results: In our study out of 100 patients mean age of 60±17.97 with Mortality rate of 16%. Total 29% patients were need ICU care. The Sensitivity, Specificity, PPV and NPV for predicting mortality and for ICU admission of Expanded CURB-65 score is found to be superior to CURB-65 Score. Conclusions: In comparison to the CURB-65 score system, the expanded CURB-65 score prioritises both clinical and laboratory criteria and is a more reliable marker for evaluating CAP severity and may improve the effectiveness of forecasting death in CAP patients.